3D Modeling and Computer Graphics in Virtual Reality - Toxirjonovich, O’rinov Nodirbek; o‘g‘li, Djuraboyev Maqsudbek Karimbek (International Journal on Orange Technologies, 2021)
In the era of digital information technologies, 3D modeling and computer graphics techniques not only apply to the development of virtual models for computer simulation, artificial intelligence (AI), big data analytics, etc., but also they can be applied in many different applications in virtual reality (VR). However, the computer graphics effect and visual realism are usually the trade-offs with the real-time and realistic interaction in VR. In this book chapter, we would like to review the general flow of the VR program development process, and the recent 3D modeling and texture painting techniques used in VR. On the other hand, we would introduce some of the key 3D modeling and computer graphics techniques that can be applied in VR in order to enhance the speed of interaction. The key techniques including smoothing techniques and mesh editing modifiers are not only useful for the designers to learn the 3D modeling process, but it also helps to create less complex mesh models maintaining good visual effects. The techniques are particularly important in the development of 3D models to satisfy the demanding computation requirement of real-time interaction in VR program.